2006
DOI: 10.1063/1.2403909
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Kelvin transport spectroscopy of fullerene peapod quantum dots

Abstract: Articles you may be interested inInfluence of electron-phonon interaction on the thermoelectric properties of a serially coupled double quantum dot system

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 25 publications
4
36
0
Order By: Relevance
“…These findings are consistent with recent transport experiments on nanotubes with encapsulated C 60 molecules [15,16] as well as with recent density functional theory calculations of spin interactions of chains of Sc@C 82 inside carbon nanotubes…”
Section: Nanotube Devicessupporting
confidence: 80%
“…These findings are consistent with recent transport experiments on nanotubes with encapsulated C 60 molecules [15,16] as well as with recent density functional theory calculations of spin interactions of chains of Sc@C 82 inside carbon nanotubes…”
Section: Nanotube Devicessupporting
confidence: 80%
“…However, it has been reported that metal particles formed during electromigration may be left in the gap, giving spurious signatures of Coulomb Blockade (CB) and Kondo physics, which are not related to the objects deposited onto the device [10][11][12][13]. A completely different system, in which difficulties in the understanding of transport data may occur, is a fullerene peapod; in this case it is not clear if the irregular structure of Coulomb diamonds is due to the encapsulated fullerene molecules or to defects or impurities in the nanotube [14].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical investigations predict pronounced changes in the electronic band structure of the nanotube [5], which is supported by the scanning tunneling microscopy [6] and photoluminescence [7] experiments. On the other hand, no fundamental perturbation in the electron system has been found in the photoemission [8] and electron transport [9] studies on peapods.…”
Section: Introductionmentioning
confidence: 99%